PENGARUH TUNTUTAN PEKERJAAN DAN TUNTUTAN KELUARGA PADA KONFLIK PEKERJAAN-KELUARGA DAN KEPUASAN KERJA KARYAWATI TENAGA ADMINISTRASI DI UNIVERSITAS NEGERI YOGYAKARTA - , RETNO PUSPA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research is aimed at identifying the influence work demand and family demand to work-family conflict and job satisfaction in the women employee. The study was conducted in Yogyakarta State University. The data collecting was conducted by distributing the quesionnaires to 75 sample. Nonprobability sampling was adopted in the sample selection method, while the technique was purposive sampling. The sampling involved 75 women employees in the administrative staff of Yogyakarta State University. The analysis tools adopted in this research included validity and reliability tests, both of which analyzed the items ofthe quesionnaire. While testing the hypothesis, the researcher adopted the t-test (independent t-test), multiple regression test and linier regression test. The result indicated that work demand will be positively related to work-family conflict and family demand will be negatively related to work-family conflict in the women employees. The data analysis for the third hypotesis indicated that work-family conflict no negatively related to job satisfaction.